EDUKASI PENTINGNYA KONSUMSI VITAMIN SERTA POLA PENERAPAN HIDUP SEHAT SEBAGAI UPAYA PENCEGAHAN COVID-19 DI KALANGAN ANAK PANTI ASUHAN - Romadhona Suci Adinda; Riska Aulia; Rizka Humaira; Tri Purwoningsih; Paula Mariana Kustiawan (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
The aim of this education was to increased public knowledge and understanding about the use of vitamins as an effort to prevent Covid-19, and encouraging the public to adopt a healthy lifestyle that can suppress the spread of the Covid-19 virus. Participants in community service are students and orphanage administrators. Consumption of vitamins and a healthy lifestyle will also affect the immune system, especially during the Covid-19 pandemic. The activity method used is the direct counseling method through interactive lectures and activity evaluations. The results of the service activities are increasing awareness of maintaining a healthy lifestyle and understanding of community service participants reaching a value of 81%. The implementation of this activity received a good response and could provide an understanding of the importance of consuming vitamins and maintaining a healthy lifestyle during the pandemic